Implementation of the "Four Magic Words" Educational Game to Improve Understanding and Application of Akhlaqul Karimah in Elementary Madrasah Students - Awalia Qolbi Isma Fadillah; Nendi Ergiansyah; Rizqi Sofiana; Tyas Endah Sulistiyanah (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This classroom action research aims to describe the implementation process, analyze practical findings, and measure the achievement of learning objectives in Islamic Religious Education (PAI) through the implementation of the educational game “Four Magic Words.” This game is designed to strengthen students’ understanding and application of simple Akhlaqul Karimah (noble character), focusing on four key expressions: thank you, sorry, please, and excuse me. The research procedure involved grouping students into teams and conducting a competitive activity to find and attach statement cards that matched the four key expressions. The results show that this game successfully stimulated students’ enthusiasm and active participation. One of the main findings was the challenge of classroom management due to students’ high energy levels, which was addressed through transition techniques and the application of Abraham Maslow’s humanistic approach to manage distractions. Theoretically, this approach integrates Behaviorist theory (through the use of rewards), Constructivist theory (through independent contextual understanding), and Integrative Learning (by combining PAI, Indonesian Language, and Social Studies). The achievement of PAI learning objectives was found to be optimal, covering cognitive aspects (students were able to identify and distinguish concepts), affective aspects (the emergence of collaboration and real-life transfer of learning in daily interactions), and psychomotor aspects (students’ agility in the game). A major indicator of success was the spontaneous use of the four magic words by students in classroom interactions, which reflects the internalization of Akhlaqul Karimah values in a simple and practical form.